PENGARUH LOKASI, BIAYA DAN FITUR LAYANAN TERHADAP KEPUASAN KONSUMEN BERTRANSAKSI PADA APLIKASI “ TOKO MODERN FASTPAY” - Juli Syahputri; Muhammad Lathief Ilhamy Nasution; Siti Aisyah (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2023)
The development of information technology, telecommunications and the internet has made business actors compete to create online or digital-based business applications. This research was conducted with the aim of knowing the Effect of Location, Fees and Service Features on Customer Satisfaction Using the fast pay Application. This research method uses quantitative methods with data collection techniques by distributing questionnaires to 96 respondents, namely customers who use services at fast pay Modern Stores. The sampling technique in this study used accidental sampling using the slovin formula. The results of the study show that: partially and simultaneously there is significant and significant influence of Location, Fees and Service Features on Customer Satisfaction in transactions using the fast pay application in Sei Pelancang village, Labuhan Batu Regency. The contributions to this study are: theoretically research can provide benefits and information as a basis for complementing customer satisfaction factors in using the fast pay application. In addition, this research can also be used as a reference to examine the influence of location, administrative costs and service features in order to create customer satisfaction and loyalty. In practice, this research can contribute to other applications in order to pay more attention to features, location and administrative costs.